Unitary Design of Quantum Spin Networks for Robust Routing, Entanglement Generation, and Phase Sensing. Issue 8 (10th July 2022) - Alsulami, Abdulsalam H.; D'Amico, Irene; Estarellas, Marta P.; Spiller, Timothy P.
Abstract: Spin chains can be used to describe a wide range of platforms for quantum computation and quantum information. They enable the understanding, demonstration, and modeling of numerous useful phenomena, such as high fidelity transfer of quantum states, creation and distribution of entanglement, and creation of resources for measurement‐based quantum processing. In this paper, a more complex spin system, a 2D spin network (SN) engineered by applying suitable unitaries to two uncoupled spin chains, is studied. Considering only the single‐excitation subspace of the SN, it is demonstrated that the system can be operated as a router, directing information through the SN. It is also shown that it can serve to generate maximally entangled states between two sites. Furthermore, it is illustrated that this SN system can be used as a sensor device able to determine an unknown phase applied to a system spin. A detailed modeling investigation of the effects of static disorder in the system shows that this system is robust against different types of disorder. Abstract : Through a unitary design process, a 2D quantum spin network (SN) is built by coupling together two spin chains. It is shown that this SN has applications for routing in quantum communications, for entanglement generation, and for sensing an unknown phase. Modeling investigations of disorder demonstrate that all these applications are very robust, and can be achieved even in the presence of significant errors.